Etiologies and hearing status in bilateral vestibulopathy: a retrospective study of 315 patients - Moyaert, Julie; Dobbels, Bieke; Peetermans, Olivier; Boon, Bram; Lucieer, Florence; Guinand, Nils; Mertens, Griet; Gilles, Annick; van de Heyning, Paul; Fornos, Angelica Pérez; van de Berg, Raymond; Van Rompaey, Vincent (Frontiers in Neurology, 2023)
Importance The development of a vestibular implant has reached milestones and seems to be a promising therapeutic tool for bilateral vestibulopathy (BV). Given the former lack of therapeutic options for BV, the disease has received scant attention in the previous research literature. It is therefore of major importance to gain more insight into the underlying pathology of BV. Furthermore, as some research groups specifically use a combined vestibulo-cochlear implant, the size of the group of BV patients with associated hearing loss is of special interest. Objectives The study aimed to determine the definite and probable etiology in bilateral vestibulopathy (BV) patients and to report on their hearing status. Design This study involves multicenter retrospective study design. Setting The research setting is at tertiary referral centers. Participants Consecutive BV patients diagnosed at the Antwerp University Hospital between 2004 and 2018 at the Maastricht University Medical Center between 2002 and 2015 and at the Geneva University Hospital between 2013 and 2018, who met the BV diagnostic criteria of the Bárány Society. Main outcome measures Primary interests were the etiology and hearing status of BV patients. Moreover, the data of vestibular tests were examined (caloric irrigation, rotatory chair tests, and video-head impulse test). Results The authors identified 315 BV patients, of whom 56% were male patients. Mean age at diagnosis was 58.6 ± 15.1 (range 7–91) years. The definite cause was determined in 37% of the patients and the probable cause in 26% of the patients. No cause was identified in 37% of BV patients. The largest subgroup included patients with genetic etiology (31%), most frequently COCH mutation. Only 21% of patients (n = 61) had bilateral normal hearing. Almost half of the patients (45%, n = 134) had profound hearing loss in at least one ear. Conclusion BV is a heterogeneous condition, with over a third of cases remaining idiopathic, and nearly three-quarters affected by hearing loss. COCH mutation is the most common non-idiopathic cause of BV in our population. Only 21% of our BV patients presented with bilateral normal hearing.